2020
DOI: 10.1080/14779072.2021.1845143
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of coronary intravascular lithotripsy for calcified coronary arteries– a systematic review and meta-analysis

Abstract: Objectives: Intravascular lithotripsy (IVL) clinical efficacy and safety in the treatment of calcified coronary artery disease (CAC) is not well known. We sought to assess IVL safety and efficacy in CAC. Methods:A comprehensive online databases search were performed to identify intravascular lithotripsy studies in patients with coronary artery disease. The primary outcome was IVL related change in the mean pre and post-procedural diameter of the coronary artery.Results: A total of 4 studies with 282 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…These findings might be linked to the decreased rate of periprocedural complications after S-IVL. Relatively lower rates of perforation were observed, and the slow/no-flow phenomena have been confirmed in the non-LM studies [ 31 , 32 , 33 ], which are also associated with the mechanism of action in S-IVL. Since lithotripsy leads to defragmentation and fractures of the calcific plaque without affecting a vessel wall, it does not generate the plaque ablation, meaning that the occurrence of the no-flow phenomenon or perforation is very unlikely.…”
Section: Discussionmentioning
confidence: 53%
“…These findings might be linked to the decreased rate of periprocedural complications after S-IVL. Relatively lower rates of perforation were observed, and the slow/no-flow phenomena have been confirmed in the non-LM studies [ 31 , 32 , 33 ], which are also associated with the mechanism of action in S-IVL. Since lithotripsy leads to defragmentation and fractures of the calcific plaque without affecting a vessel wall, it does not generate the plaque ablation, meaning that the occurrence of the no-flow phenomenon or perforation is very unlikely.…”
Section: Discussionmentioning
confidence: 53%
“…Early non-randomized observational studies, such as the Disrupt CAD I, II, III and IV and the Disrupt PAD I and II trials, have shown that the IVL system is a safe and effective option for the preparation and dilation of highly calcified lesions in coronary and femoropopliteal arteries that are difficult to treat with conventional endovascular techniques. 3,[7][8][9][10][11] To date, the only randomized controlled trial with the IVL system is the Disrupt PAD III trial. 7 In this single-blind study, patients with arterial insufficiency due to calcified superficial femoral or popliteal lesions received vessel preparation with the IVL system or a plain balloon percutaneous transluminal angioplasty (PTA), followed by stenting or drug coated balloon application if required.…”
Section: Discussionmentioning
confidence: 99%
“…Six-hundred seventy-nine of the 976 enrolled patients had the locations of their lesion (s) identified. Four-hundred thirty-six patients had a single identified lesion, either in the common iliac artery (77), external iliac artery (17), left iliac artery (3), right iliac artery (4), common femoral artery (66), superficial femoral artery (191), popliteal artery (79), unnamed infrapopliteal vessel (5), anterior tibial artery (47), posterior tibial artery (26), tibioperoneal trunk (40), or the peroneal artery (21). Sixty-two patients had multiple lesions treated, including 47 with both the common and external iliac artery, 5 with both the superficial femoral and popliteal artery, 9 with the anterior tibial, posterior tibial and peroneal arteries, 27 and 1 with the anterior tibial and posterior tibial arteries.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…[16][17][18] The technology emits high-intensity sonic pressure waves into the body to fragment stones without harming surrounding important soft tissue. 19 Over the past decade, this technology has been adapted to break up calcified plaques and improve the compliance of vasculature in patients with cardiovascular disease [20][21][22] and now in more recent years, has been used in patients with PAD. Termed intravascular lithotripsy (IVL) (Shockwave Medical, Fremont, California, United States), 23 the novel application of this existing technology serves as an adjunctive minimally invasive endovascular treatment for calcified plaques in the lower extremities of patients.…”
Section: Introductionmentioning
confidence: 99%